"Blacks in the city Lima (1815 - 1820)" Interethnic coexistence and social danger - Ortega Luján, Betzabeth (2007)
The aim of this paper is to analyze, describe and explain how does the political, economic and social context of the city of Lima, during the first decades of the XIX century influenced in the behaviour and attitudes of black people (both slaves and free men). It is shown how the need for satisfying their personal needs allowed the creation and development of economic mechanisms that allowed black people to get stability and permanence. The inevitable closeness between social groups implied a necessary interethnic coexistence that illustrates the situation of free men and slaves that lived in the city. The degree of social danger that the city reached was also generated by this facts. In this research, the XIX century documents and files have been reviewed and catalogued. In addition, heuristic and hermeneutic methods were used in order to recollect and organize data.